2018
DOI: 10.1021/acsami.8b07786
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Dielectric Properties of LaNiO3/BaTiO3/PVDF: A Three-Phase Percolative Polymer Nanocrystal Composite

Abstract: Polymer (poly(vinylidene fluoride) (PVDF)) nanocrystal composites based on lanthanum nickelate (percolative oxide) and barium titanate were fabricated to obtain material systems with a high dielectric constant and low loss to be used for high-charge-storage applications. Lanthanum nickelate (LaNiO) nanocrystallites were synthesized from a simple citrate-assisted sol-gel route that yielded agglomerated crystallites of an average size of 120 nm. The defective nature of the lanthanum nickelate nanocrystals was re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 53 publications
2
14
0
Order By: Relevance
“…When a fine linear fitting (adjusted R 2 of the fitting was 0.99) was made onto the data in Figure 4 b, the u value could be achieved as 1.02 for the sample. As expected, this u value (1.02) was much higher than the universal u value (0.70) [ 48 ] predicted by percolation theory. The gap between the two u values was calculated to be 0.32, which may be attributed to the contribution of induced polarization to the ac conductivity of this sample.…”
Section: Resultssupporting
confidence: 56%
See 1 more Smart Citation
“…When a fine linear fitting (adjusted R 2 of the fitting was 0.99) was made onto the data in Figure 4 b, the u value could be achieved as 1.02 for the sample. As expected, this u value (1.02) was much higher than the universal u value (0.70) [ 48 ] predicted by percolation theory. The gap between the two u values was calculated to be 0.32, which may be attributed to the contribution of induced polarization to the ac conductivity of this sample.…”
Section: Resultssupporting
confidence: 56%
“…As the volume concentration of conducting filler is near the percolation threshold, the ac conductivity ( σ ) of composite has much to do with the angular frequency ( ω ) of the applied ac electric field ( ω = 2π f , f is measuring frequency). The relation has been expressed as ‘ σ ∝ ω u ’ ( u is the critical exponent) [ 48 ]. In Figure 4 b, the relation between log( σ ) and log( ω ) for the SiC-0.29/PVA sample was obtained, based on the known data in Figure 4 a.…”
Section: Resultsmentioning
confidence: 99%
“…This clearly indicated that the effect of interfacial polarisation on the enhanced 3 0 values was dominant, especially for the LSNO-2/PVDF composite, as a result of their percolative nature. Such a drastic increase in the 3 0 value for the LSNO-2/PVDF composite could also be rationalised by the micro-capacitor model, 33,42 which considers the consistency of a network of several micro-capacitors formed by a thin layer of PVDF polymer between two neighbouring LSNO-2 particles, where each of these micro-capacitors contributes to an abnormally high capacitance. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Hu et al designed the polypropylene composites co-filled with semi-conductive tetra-needle-shaped zinc oxide whiskers (ZnO) and barium titanate (BT) nanoparticles, 37 where an improvement of dielectric permittivity (from 8.5 to 11) and a decline of loss tangent (from 0.008 to 0.004) could be realized simultaneously. Jaschin et al constructed a ternary percolative polymer composite consisting of lanthanum nickelate (LaNiO3) nanocrystals, barium titanate (BaTiO3) nanocrystals and polyvinylidene fluoride, 38 a high dielectric constant of 90 at 10 kHz (and a low loss of 0.13) was obtained with the LaNiO3 content below the percolation threshold. The achieved dielectric constant is around 9 times that of pure PVDF and 3 times that of BaTiO3/PVDF nanocomposite.…”
Section: Introductionmentioning
confidence: 99%